Degree of Adaptation to International Financial Reporting Standards: The Case of Turkey - Sabuncu, Birsel (European Scientific Journal, ESJ, 2017)
With International Financial Reporting Standards (IFRS) a contribution is made to create a common language between the countries in accounting science and to constitute accounting provisions. Our country has not stayed away from this common language and currently, the studies on accounting science are underway. Public Oversight Accounting and Auditing Standards Authority have the International Financial Reporting Standards (IFRS) Turkish Accounting Standards translated into Turkish and published such as Turkish Accounting Standards /Turkish Financial Reporting Standards (TAS/TFRS) are as published. These are the Turkish translation of International Accounting/ Financial Reporting Standards. Now, in our country, a binary system is still used as Uniform Accounting System as well as TAS/TFRS are in ongoing process. There are different approaches towards the economy in terms of the standards and the Uniform Chart of Accounts and it is required to improve the current system and harmonize the Uniform Chart of Accounts with the standards.